Cinematic “pas de deux”: the dialogue between Maya Deren's experimental filmmaking and Talley Beatty's black ballet dancer in A Study in Choreography for Camera (1945) - Durkin, Hannah (Cambridge University Press, 2013)
A Study in Choreography for Camera (1945) is a collaborative enterprise between avant-garde filmmaker Maya Deren and African American ballet dancer Talley Beatty. Study is significant in experimental film history – it was one of three films by Deren that shaped the emergence of the postwar avant-garde cinema movement in the US. The film represents a pioneering cross-cultural and cross-disciplinary dialogue between Beatty's ballet dancing and Deren's experimental cinematic technique. The film explores complex emotional experiences through a cinematic re-creation of Deren's understanding of ritual (which she borrowed from Katherine Dunham's Haitian experiences after spending many years documenting vodou) while allowing a leading black male dancer to display his artistry on-screen. I show that cultures and artistic forms widely dismissed as incompatible are rendered equivocal. Study adopts a stylized and rhythmic technique borrowed from dance in its attempt to establish cinema as “art,” and I foreground Beatty's contribution to the film, arguing that his technically complex movements situate him as joint author of its artistic vision. The essay also explores tensions between the artistic intentions of Deren, who sought to deprivilege the individual performer in favour of the filmic “ritual,” and Beatty, who sought to display his individual skills as a technically accomplished dancer.